2013
DOI: 10.1098/rstb.2012.0023
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution single-molecule characterization of the enzymatic states in Escherichia coli F 1 -ATPase

Abstract: The rotary motor F 1 -ATPase from the thermophilic Bacillus PS3 (TF 1 ) is one of the best-studied of all molecular machines. F 1 -ATPase is the part of the enzyme F 1 F O -ATP synthase that is responsible for generating most of the ATP in living cells. Single-molecule experiments have provided a detailed understanding of how ATP hydrolysis and synthesis are coupled to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 57 publications
(128 reference statements)
4
81
1
Order By: Relevance
“…Analyzing mutant enzymes with Lys and Cys at position 376 of the a subunit, we concluded that aArg376 does not play a catalytic role, but is important for conformational transmission among the three sites, as discussed in detail previously (5,29). bGlu185 located near aArg376 in the catalytic site is also close to the phosphate moiety of ATP in the crystal structure (17). All substitution mutants of this residue lost the catalytic cooperativity, although they retained the ability of unisite catalysis (30).…”
Section: Mutational Studies On F-atpasesupporting
confidence: 57%
See 2 more Smart Citations
“…Analyzing mutant enzymes with Lys and Cys at position 376 of the a subunit, we concluded that aArg376 does not play a catalytic role, but is important for conformational transmission among the three sites, as discussed in detail previously (5,29). bGlu185 located near aArg376 in the catalytic site is also close to the phosphate moiety of ATP in the crystal structure (17). All substitution mutants of this residue lost the catalytic cooperativity, although they retained the ability of unisite catalysis (30).…”
Section: Mutational Studies On F-atpasesupporting
confidence: 57%
“…ATP waiting and catalytic dwells were confirmed with the E. coli enzyme (17,18). The rotation of the c 10 ring in F O can be also followed using gold beads, the rate being about $200 rps (M. Sekiya, H. Hosokawa, and M. Futai, unpublished observation).…”
Section: Figmentioning
confidence: 85%
See 1 more Smart Citation
“…The time scale with the three substeps (∼40 ms) agrees well with the experimental values (∼50 ms; ∼60 s −1 for a 120°step) at a maximum load condition (4). This result suggests a possible third substep, yet unresolved, for the E. coli F 1 (34,35). This third step could be associated with phosphate release (31,36).…”
Section: Significancementioning
confidence: 90%
“…The two most heavily studied bacterial F 1 ATPases come from the thermophile Bacillus PS3 (TF 1 ) and the mesophile Escherichia coli (EF 1 ). Both enzymes are capable of ATP hydrolysis activity, rotating stepwise at an ATP concentration-dependent rate in an anticlockwise direction (23,40). Because the hexameric ␣ 3 ␤ 3 structure harbors three catalytic sites, the basic step size is 120°coupled to either the consumption or production of one ATP molecule (41).…”
mentioning
confidence: 99%